Ethnomethodological approach to address school violence in a basic education institution - Leal-Leal, Gisela (2023)
Addressing school violence requires the active participation and commitment of the entire educational community. This qualitative ethnomethodological research proposes a participatory pedagogical design aimed at disarticulating it, based on its understanding by institutional actors, from the data of the interview conducted with 282 students in a public educational institution in the city of Cúcuta in Colombia. The findings show that students associate violence with physical and verbal abuse, understand coexistence as the result of complying with institutional rules, and show interest in promoting respect among themselves and with their teachers. A pedagogical proposal is proposed based on the axes of peace, violence and conflict, aimed at raising awareness of the phenomenon of violence and the collective construction of its approach by school actors.